Effect of the sapphire substrate on spectral emission features of LEDs based on InGaN/AlGaN/GaN heterostructures - Bletskan, D.I.; Lukyanchuk, O.R.; Bletskan, O.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Luminescence spectra of blue and green LEDs based on InxGa₁₋xN/AlyGa₁₋yN/GaN heterostructures with many quantum wells in the current range 0.1 to 10 mA have been studied besides the main electroluminescence band. In the emission spectra of blue LEDs, the energy maximum position is shifted with changing the current (hn max = 2.62 - 2.63 eV). A weak doublet of R-lines 692.8 and 694.3 nm conditioned by the re-emission of single Cr³⁺ ions in a sapphire substrate has been fixed. The use of substrates from heavy doped ruby for making white LEDs based on nitride heterostructures has been proposed. The expediency of using blue and green LEDs as sources of photoluminescence excitation in the range of R- and N-lines of sapphire substrates and heavy doped ruby has been shown.